Իրավաչափ վարքագիծը որպես իևավական մշակույթի արտահայտման հիմնական ձև և չափանիշ - Բարխուդարեանց, Սերգեյ (Լիմուշ հրատ.)
This article presents the legal code of contract as a basic form and measurement of the expression of legal culture. The author defines the essence of the legal code of the contract, its distinctive features, objective and subjective components, external and subjective aspects, forms of conclusion, and the role of the legal code of contrast in solving urgent problems of public interest.
Keywords: Իրավունք